Process of Making Liquid Organic Fertilizer in Biotechnology Material - Syllistiana, Lina (Balai Publikasi Indonesia, 2025)
Organic fertilizer is a fertilizer made from organic materials such as the decay of plant, animal, and human remains. This study aims to determine the process of making liquid organic fertilizer in biotechnology material. The method of making this liquid organic fertilizer is that household organic waste such as vegetable waste, fruit peels, and others are separated from inorganic waste, then added with EM4 bio activator. Based on the results of the experiment, an environmentally friendly organic fertilizer can be produced that can be used to increase agricultural production both in terms of quality and quantity, reduce environmental pollution, improve land quality sustainably, increase land productivity and can prevent land degradation